The Association Between BMI, Depression, and Post-Acute Sequelae of COVID-19 (PASC) among Nurses in Lamongan, Indonesia - Abdul Rokhman; Nur Hidayati Madzkur; Faizul Hasan; Nurul Chayatin (Babali Nursing Research, 2022)
Introduction: Most nurses who were infected by COVID-19 experienced Post-acute Sequelae of COVID-19. Post-acute Sequelae of COVID-19 has caused fatigue, shortness of breath, memory impairment, and joint pain which make nurses unable to work optimally. Objective: This research aimed to analyze the association between BMI, depression, and post-acute sequelae of COVID-19 among nurses in Lamongan, Indonesia. Methods: This was a cross-sectional research which involved all nurses in Lamongan who were infected by COVID-19. The samples were obtained by purposive sampling from June to July 2022. The data were gathered by using questionnaires. Depression was measured by PHQ-9 questionnaire to which then analyzed by logistic regression test (α≤0.05). Results: A total of 226 nurses who were infected by COVID-19 participated in this study. From the number, 45.1% were males and 54.9% were females. 96% were working in the health services while 4% were working in the educational institutions. 17.6% had history of diseases while 82.4% had no history of diseases. The results indicated that gender was not associated with both sequelae of cough and fatigue (p>0.05). BMI was not associated with either sequelae of cough or fatigue (p>0.05). Depression did not affect sequelae of cough (p=0.62), but nurses who experienced depression were 0.12 times at risk of experiencing fatigue (p=0.02). Conclusion: It can be concluded that depression is a factor which increases fatigue.